Ochotona princeps - Robert S. Hoffmann (Smithsonian Institution Press, 1993)
Ochotona princeps (Richardson, 1828). Zool. J., 3:520. TYPE LOCALITY: "Rocky Mountains"; restricted by Preble (1908) to "near the sources of Elk (Athabasca) River," [Athabasca Pass, head of Athabasca River, Alberta, Canada]. DISTRIBUTION: Mountains of W North America from C British Columbia (Canada) to N New Mexico, Utah, C Nevada, and EC California (USA). STATUS: Most populations are not currently threatened, except for a few isolates in the Great Basin (goldmani, obscura, nevadensis, tutelata); tutelata may now be extinct (A. T. Smith et al., 1990). SYNONYMS: albata Grinnell, 1912; barnesi, Durrant and Lee, 1955; brooksi Howell, 1924; brunnescens Howell, 1919; cinnamomea Allen, 1905; clamosa Hall and Bowlus, 1938; cuppes Bangs, 1899; fenisex Osgood, 1913; figginsi Allen, 1912; fumosa Howell, 1919; fuscipes Howell, 1919; goldmani Howell, 1924; howelli Borell, 1931; incana Howell, 1919; jewetti Howell, 1919; lasalensis Durrant and Lee, 1955; lemhi Howell, 1919; levis Hollister, 1912; littoralis Cowan, 1955; lutescens Howell, 1919; minimus Lord, 1863; moorei Gardner, 1950; muiri Grinnell and Storer, 1916; nevadensis Howell, 1919; nigrescens Bailey, 1913; obscura Long, 1965; saturata Cowan, 1955; saxatilis Bangs, 1899; schisticeps (Merriam, 1889); septentrionalis Cowan and Racey, 1947; sheltoni Grinnell, 1918; taylori Grinnell, 1912; tutelata Hall, 1934; uinta Hollister, 1912; utahensis Hall and Hayward, 1941; ventorum Howell, 1919; wasatchensis Durrant and Lee, 1955. COMMENTS: Broadbooks (1965) and Youngman (1975) considered princeps and collaris conspecific. Corbet (1978c), following Gureev (1964) included princeps in alpina. A statistical réévaluation of craniometric data by Weston (1981) indicated that princeps, collaris, and alpina are separate species. Reviewed by Smith and Weston (1990, Mammalian Species, 352). Published as part of Robert S. Hoffmann, 1993, Order Lagomorpha, pp. 807-827 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 811, DOI: ...